Pengaruh Kompetensi terhadap Kinerja Pendamping Lokal Desa di Wilayah Kepulauan - Ibis Ali; Aida Vitayala S Hubeis; Anna Fatchiya (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Local village facilitators have a role in increasing the capacity and effectiveness of government and village communities. The competence and performance of local village assistants can measure the success of village assistance. Quantitative research using this survey method aims to describe individual characteristics, determine the level of competence and performance and analyze the effect of competence on the performance of local village assistants. The research was conducted in July and August 2022 in Banggai Kepulauan and Banggai Laut Regencies with 40 local village facilitators as respondents. The variables of this study are competencies supported by technical, managerial, and socio-cultural competency indicators. In contrast, performance variables include managing village development, local economic development, increasing village community participation, and mentoring evaluation. Data collection techniques are through questionnaires, interviews, and observation. Data analysis was performed using the SEM-PLS (Structural Equation Modeling-Partial Least Square) method using the SmartPLS 3.29 application. The results showed that respondents were dominated by male aged 38-48 years, high school education level, high years of service, low non-formal education, and many assisted villages. Assistants have high competence and performance. There is no real difference between the competence and performance of assistants in the Banggai Laut and Banggai Kepulauan Regencies. There is a strong influence between competence on the performance of local village assistants. Therefore, the advice is that the assistants' competence needs to be improved through training and mentoring to achieve good work results.